COVID-19 emergency response assessment study: a prospective longitudinal survey of frontline doctors in the UK and Ireland: study protocol - Daniel Horner; Jo Daniels; Charles Reynard; Blair Graham; Mark David Lyttle; Michael Barrett; Edward Carlton; Tom Roberts; William Hulme; Katie Samuel; Robert Hirst (BMJ Open)
Introduction The COVID-19 pandemic is putting an unprecedented strain on healthcare systems globally. The psychological impact on frontline doctors of dealing with the COVID-19 pandemic is currently unknown. This longitudinal professional survey aims to understand the evolving and cumulative effects of working during the COVID-19 outbreak on the psychological well-being of doctors working in emergency departments (ED), intensive care units (ICU) and anaesthetics during the pandemic.Methods and analysis This study is a longitudinal questionnaire-based study with three predefined time points spanning the acceleration, peak and deceleration phases of the COVID-19 pandemic.The primary outcomes are psychological distress and post-trauma stress as measured by the General Health Questionnaire-12 (GHQ-12) and Impact of Events Scale-Revised (IES-R). Data related to personal and professional characteristics will also be collected. Questionnaires will be administered prospectively to all doctors working in ED, ICU and anaesthetics in the UK and Ireland via existing research networks during the sampling period. Data from the questionnaires will be analysed to assess the prevalence and degree of psychological distress and trauma, and the nature of the relationship between personal and professional characteristics and the primary outcomes. Data will be described, analysed and disseminated at each time point; however, the primary endpoint will be psychological distress and trauma at the final time point.Ethics and dissemination Ethical approval was obtained from the University of Bath, UK (ref: 4421), and Children’s Health Ireland at Crumlin, Ethics Committee. Regulatory approval from the Health Regulation Authority (UK), Health and Care Research Wales (IRAS: 281944).This study is limited by the fact that it focuses on doctors only and is survey based without further qualitative interviews of participants. It is expected this study will provide clear evidence of the psychological impact of COVID-19 on doctors and will allow present and future planning to mitigate against any psychological impact.Trial registration number ISRCTN10666798.